Towards Third-Generation Living Lab Networks in Cities - Seppo Leminen; Mervi Rajahonka; Mika Westerlund (Technology Innovation Management Review, 2017)
Many cities engage in diverse experimentation, innovation, and development activities with a broad variety of environments and stakeholders to the benefit of citizens, companies, municipalities, and other organizations. Hence, this article discusses such engagement in terms of next-generation living lab networks in the city context. In so doing, the study contributes to the discussion on living labs by introducing a framework of collaborative innovation networks in cities and suggesting a typology of third-generation living labs. Our framework is characterized by diverse platforms and participation approaches, resulting in four distinctive modes of collaborative innovation networks where the city is: i) a provider, ii) a neighbourhood participator, iii) a catalyst, or iv) a rapid experimenter. The typology is based on an analysis of 118 interviews with participants in six Finnish cities and reveals various ways to organize innovation activities in the city context. In particular, cities can benefit from innovation networks by simultaneously exploiting multiple platforms such as living labs for innovation. We conclude by discussing implications to theory and practice, and suggesting directions for future research.
Keywords: city; co-creation; collaborative innovation; innovation; Living lab; networks; Open innovation; smart city; third-generation

Technological Public–Private Innovation Networks: A Conceptual Framework Describing Their Structure and Mechanism of Interaction - Rabeh Morrar (Technology Innovation Management Review, 2015)
Technological public–private innovation networks, or TechPPINs, enable cooperation between public and private actors in a complex, dynamic, social, and interactive network structure. In this article, the literature on innovation networks is used to construct a conceptual framework that describes the structure and mechanism of interaction in technological public–private innovation networks. In the framework, innovation is created through a dynamic process of interaction between the public and private actors along the network lifecycle. In each stage of network lifecycle, social capital enables various interactions to occur and different modes and quantities of knowledge and technological resources to be exchanged and reinforced. Through a combination of the product lifecycle model and social network analysis, the structure of technological public-private innovation networks are examined at each stage of the lifecycle to reveal information about how the roles of public and private actors are embodied.
Keywords: conceptual framework; innovation networks; network lifecycle; networks; public–private partnership; social network analysis; technological public–private innovation networks; TechPPINs

Actor Roles in an Urban Living Lab: What Can We Learn from Suurpelto, Finland? - Soile Juujärvi; Kaija Pesso (Technology Innovation Management Review, 2013)
There is a growing trend to involve citizens in city development to make urban areas more suitable to their needs and prevent social problems. City centres and neighbourhoods have increasingly been serving as regional living labs, which are ideal platforms to explore the needs of users as residents and citizens. This article examines the characteristics and success factors of urban living labs based on a case study of Suurpelto, Finland. Urban living lab activity is characterized by a practice-based innovation process with diffuse and heterogeneous knowledge production that aims to address urban problems of varying complexity. User involvement is critical for co-creating value, but equally important is collaboration between other living lab actors: enablers, providers, and utilizers. Enabler-driven labs can be successful in creating common goals but they need providers, such as development organizations, to boost development. Proactive networking, experimentation as a bottom-up process, using student innovators as resources, as well as commitment and longevity in development work are success factors for urban living labs.
Keywords: innovation; knowledge production; networks; regional development; urban living labs

Editorial: Living Labs (November 2013) - Chris McPhee; Seppo Leminen; Mika Westerlund (Technology Innovation Management Review, 2013)
Keywords: design; living labs; networks; Open innovation; regional development; services

Living Labs as Open-Innovation Networks - Seppo Leminen; Mika Westerlund; Anna-Greta Nyström (Technology Innovation Management Review, 2012)
Living labs bring experimentation out of companies’ R&D departments to real-life environments with the participation and co-creation of users, partners, and other parties. This study discusses living labs as four different types of networks characterized by open innovation: utilizer-driven, enabler-driven, provider-driven, and user-driven. The typology is based on interviews with the participants of 26 living labs in Finland, Sweden, Spain, and South Africa. Companies can benefit from knowing the characteristics of each type of living lab; this knowledge will help them to identify which actor drives the innovation, to anticipate likely outcomes, and to decide what kind of role they should play while "living labbing". Living labs are networks that can help them create innovations that have a superior match with user needs and can be upscaled promptly to the global market.
Keywords: co-creation; innovation; living labs; networks; Open innovation

Living Labs for Cross-Border Systemic Innovation - Hans Schaffers; Petra Turkama (Technology Innovation Management Review, 2012)
Innovation is increasingly taking place in cross-border collaborative networks, which are shaped by the characteristics of systemic innovation, the strategies and objectives of main actors, and the dynamics of the innovation process. Participation in such networks is of high importance for small firms, but requires long-term investments and a diverse range of collaboration and innovation capabilities. This article explores how living labs, understood as innovation projects based on open and user-centric innovation methodologies, can form collaboration networks to support small firms and other actors to engage in cross-border collaboration and to accelerate the development and acceptance of innovations. Based on the lessons learned from a major living lab project, APOLLON, we conclude that adopting the living labs networking approach requires thorough understanding of each party’s objectives and drivers, the alignment of operational processes, establishment of open and collaborative culture, as well as competences, methods, and tools for supporting cooperation and community building.
Keywords: collaboration; innovation; living labs; networks; systemic

The Impact of External Relationships on the Growth of Young Technology Companies - Chris Justus (Technology Innovation Management Review, 2011)
Most management teams in young technology companies are aware that their success may depend on strong relationships with external organizations. However, it may not be clear to them which types of relationships are most likely to impact their growth. This article describes the author’s recent research to examine the relationship between the number and diversity of business relationships and the revenue growth of young companies. By examining data collected from 80 technology firms, and the 1943 relationships they established over a two-year period, certain types of relationships were found to have measurable impacts on growth. The article focuses on the managerial implications of these findings, which include the importance of early funding, niche identification, and building relationships with large firms.
Keywords: funding; networks; partnerships; relationships; startups; young companies